Caffeine and sprinting performance: Dose responses and efficacy - Glaister, M.; Patterson, S. D.; Foley, P.; Pedlar, C. R.; Pattinson, J. R.; McInnes, G. (The Journal of Strength and Conditioning Research, 2012)
The aims of this study were to evaluate the effects of caffeine supplementation on sprint cycling performance and to determine if there was a dose-response effect. Using a randomized, double-blind, placebo-controlled design, 17 well-trained men (age: 24 ± 6 years, height: 1.82 ± 0.06 m, and body mass(bm): 82.2 ± 6.9 kg) completed 7 maximal 10-second sprint trials on an electromagnetically braked cycle ergometer. Apart from trial 1 (familiarization), all the trials involved subjects ingesting a gelatine capsule containing either caffeine or placebo (maltodextrin) 1 hour before each sprint. To examine dose-response effects, caffeine doses of 2, 4, 6, 8, and 10 mg·kg/bm were used. There were no significant (p > 0.05) differences in baseline measures of plasma caffeine concentration before each trial (grand mean: 0.14 ± 0.28 µg/ml). There was, however, a significant supplement × time interaction (p < 0.001), with larger caffeine doses producing higher postsupplementation plasma caffeine levels. In comparison with placebo, caffeine had no significant effect on peak power (p = 0.11), mean power (p = 0.55), or time to peak power (p = 0.17). There was also no significant effect of supplementation on pretrial blood lactate (p = 0.58), but there was a significant time effect (p = 0.001), with blood lactate reducing over the 50 minute postsupplementation rest period from 1.29 ± 0.36 to 1.06 ± 0.33 mmol/L. The results of this study show that caffeine supplementation has no effect on short-duration sprint cycling performance, irrespective of the dosage used.